Olmesartan alleviates SARS-CoV-2 envelope protein induced renal fibrosis by regulating HMGB1 release and autophagic degradation of TGF-β1 - Zhou, Shilin; Yu, Zanzhe; Chen, Zihui; Ning, Fengling; Hu, Xuetao; Wu, Tiangang; Li, Mingxue; Xin, Hong; Reilly, Svetlana; Zhang, Xuemei (Frontiers in Pharmacology, 2023)
Background and aims: Renal damage in severe coronavirus disease 2019 (COVID-19) is highly associated with mortality. Finding relevant therapeutic candidates that can alleviate it is crucial. Angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin-receptor blockers (ARBs) have been shown to be harmless to COVID-19 patients, but it remains elusive whether ACEIs/ARBs have protective benefits to them. We wished to determine if ACEIs/ARBs had a protective effect on the renal damage associated with COVID-19, and to investigate the mechanism. Methods: We used the envelope (E) protein of severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) to induce COVID-19-like multiple organ damage and observed renal fibrosis. We induced the epithelial–mesenchymal transformation of HK-2 cells with E protein, and found that olmesartan could alleviate it significantly. The protective effects of olmesartan on E protein-induced renal fibrosis were evaluated by renal-function assessment, pathologic alterations, inflammation, and the TGF-β1/Smad2/3 signaling pathway. The distribution of high-mobility group box (HMGB)1 was examined after stimulation with E protein and olmesartan administration. Results: E protein stimulated HMGB1 release, which triggered the immune response and promoted activation of TGF-β1/Smad2/3 signaling: both could lead to renal fibrosis. Olmesartan regulated the distribution of HMGB1 under E protein stimulation. Olmesartan inhibited the release of HMGB1, and reduced the inflammatory response and activation of TGF-β1/Smad2/3 signaling. Olmesartan increased the cytoplasmic level of HMGB1 to promote the autophagic degradation of TGF-β1, thereby alleviating fibrosis further. Conclusion: Olmesartan alleviates E protein-induced renal fibrosis by regulating the release of HMGB1 and its mediated autophagic degradation of TGF-β1.